Comparing The Hematological Effects of BPaL/BPaLM Regimens to Those of Standard Regimens in the Treatment of Drug-Resistant Tuberculosis: A Narrative Review - Apgar, Satrias; Suryani (Pharmacon: Jurnal Farmasi Indonesia, 2025)
Drug-resistant tuberculosis (DR-TB) is a problem for health around the world, and standard treatments don't work very well. The new treatment plan that includes bedaquiline, pretomanid, and linezolid (BPaL) and its variant with moxifloxacin (BPaLM) has a shorter treatment time and higher success rates, but there is still a chance of hematological side effects. Based on recent studies, this article looks at the hematological effects of BPaL/BPaLM regimens compared to standard regimens in DR-TB therapy in great detail. The study found that BPaL/BPaLM has a different effect on blood cells than standard regimens. It increases the risk of anemia (31.9% vs. 25.4%) and thrombocytopenia (47.8% vs. 23.1%), but it lowers the risk of leukopenia (2.2% vs. 14.6%). The main way that BPaL/BPaLM causes hematological toxicity by linezolid is affecting mitochondrial dysfunction, activating inflammatory pathways, and throwing off iron homeostasis. BPaL/BPaLM is a better choice because it has a shorter treatment time (24–26 weeks vs. 78–96 weeks) and fewer pills (923–924 vs. 5,460–7,296). However, it does require close monitoring of blood levels. A thorough understanding of the hematological effects of the BPaL/BPaLM regimen makes it easier to handle side effects and makes DR-TB treatment more likely to work.